Seni Permainan Tradisional Dengkleng (Engklek) Sebagai Pembentuk Karakter Pada Siswa Sekolah Dasar - Ida Bagus Putu Eka Suadnyana (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
Globalization does not only set aside forms of local wisdom but can fade the values of a nation's culture, such as the value of honesty. Therefore, it is necessary to revive a local culture that is full of honest values that can be instilled in elementary school-age children. One of the local wisdom cultures that helps create the nation's character is by cultivating traditional Balinese games. This research was conducted to analyze why the Dengkleng (Engklek) Traditional Game is still being carried out by students of SD 6 Sukawati, analyze the educational value contained in the Dengkleng (Engklek) Traditional Game and analyze the implications of the Dengkleng (Engklek) Traditional Game for students in Elementary School 6 Sukawati. The theory used to solve this research problem is role theory, humanistic theory and behavioristic theory. This research is in the form of a qualitative design with a socio-cultural approach.